PENINGKATAN HASIL BELAJAR PESERTA DIDIK DENGAN MENGGUNAKAN MEDIA AUDIO VISUAL PADA MATA PELAJARAN IPA DI KELAS IIISDN 50 BULU DATU PALOPO - Arlianti, Arlianti (Institut Agama Islam Negeri Palopo, 2019)
The purpose of this study was to determine the use of audio-visual media that can improve science learning outcomes in the third grade of SD 50 Bulu Datu. This research is classroom action research (PTK) with qualitative and quantitative research types consisting of two cycles each cycle 3 meetings, data collection techniques carried out by observing, testing, documentation with the stages of planning, implementation, observation, reflection. The results showed that: by using audio-visual media in science learning the learning outcomes of students increased, it can be seen in the data obtained which showed that the average value in class III in the first cycle reached 73 but there were still several students who are still lacking and the researchers proceed to cycle II, the learning outcomes of students increase with the results of the average score reaching 95 based on minimum completeness criteria (KKM) in science subjects have achieved results and researchers end this research until the second cycle.